Aqueous synthesis of highly luminescent CdSe quantum dots with narrow spectra using hydrazine hydrate reduction selenium. (1st March 2014) - Lan, Yuwei; Yang, Kun; Wang, Yilin; Li, Huaimei
Abstract : Highly luminescent CdSe quantum dots (QDs) with narrow spectra were synthesised by the reaction of CdCl2 ·2.5H2 O, Se and hydrazine hydrate (N2 H4 ·H2 O), respectively, in water and in the presence of 3‐mercaptopropionic acid as the stabiliser. The effects of the experimental conditions, including the refluxing time and the selenium to cadmium molar ratio, on the luminescent properties of the obtained QDs have been investigated. Furthermore, the obtained QDs were characterised by UV–vis absorption spectra, photoluminescence (PL) spectra, X‐ray powder diffraction and transmission electron microscopy, respectively. The results showed that the proposed method led to the formation of the cubic CdSe QDs with a narrow fluorescence full‐width at half‐maximum (47 nm) and a high PL quantum yield (up to 16%), respectively.